Accountability Of Socail Responsibility And Its Impact On The Performance Of Workers In Algerian Economic Institutions - saadi, abdelhak; zarour, naima (Journal of Research in Finance and Accounting, 2021)
This study aims to clarify the effect of applying social responsibility accounting on the performance of workers in Algerian economic institutions, by addressing general concepts about social responsibility accounting and the performance of workers in the theoretical framework of the study, based on the descriptive and analytical approach, and to achieve the objectives of the study, a case study method was adopted. Which is represented in the performance of the questionnaire (the questionnaire), as it was distributed to a group of accountants and financiers for several economic institutions in the state of Biskra, whose number is (30) individuals, and for data analysis and hypothesis testing the study was used the statistical program (Spss.v26), and this study concluded that Measurement and accounting disclosure of social responsibility towards employees do not affect the level of performance of employees in the institutions under study.